Achieving Biocompatible SABRE: An in vitro Cytotoxicity Study. (18th January 2018) - Manoharan, Anand; Rayner, Peter J.; Iali, Wissam; Burns, Michael J.; Perry, V. Hugh; Duckett, Simon B.
Abstract: Production of a biocompatible hyperpolarized bolus for signal amplification by reversible exchange (SABRE) could open the door to simple clinical diagnosis via magnetic resonance imaging. Essential to successful progression to preclinical/clinical applications is the determination of the toxicology profile of the SABRE reaction mixture. Herein, we exemplify the cytotoxicity of the SABRE approach using in vitro cell assays. We conclude that the main cause of the observed toxicity is due to the SABRE catalyst. We therefore illustrate two catalyst removal methods: one involving deactivation and ion‐exchange chromatography, and the second using biphasic catalysis. These routes produce a bolus suitable for future in vivo study. Abstract : Catalyst removal options : It is possible to head toward the destination, in vivo imaging under SABRE with biocompatibility, via two routes. One requires quenching of catalyst and separation via an ion‐exchange column. The second route, biphasic catalysis, employs the aqueous phase, and no catalyst is carried forward. Upon exiting, a biocompatible medium is achieved.